Internet of Musical Things Environments and Pure Data: A Perfect Match? - Vieira Costa, Rômulo Augusto; Schiavoni, Flávio Luiz (Cultural Arts Research and Development, 2024)
The Internet of Musical Things (IoMusT) is an emerging area based on concepts from the Internet of Things, new interfaces for musical expression, human-computer interaction, ubiquitous music, and many others. Despite being a novelty, it already has some ecosystem models that use their abstractions to allow musical practice. However, they are not standardized and tend to consider only the preferences of their creators, relegating Pure Data, when present, to a secondary role. In this context, this article presents the Sunflower environment, a tool created by the authors of this text and which uses Pure Data in all its development stages, highlighting the importance of such a tool.